2021
DOI: 10.1055/s-0041-1728831
|View full text |Cite
|
Sign up to set email alerts
|

Oxford-AstraZeneca ChAdOx1 COVID-19 Vaccine Does Not Alter Platelet Aggregation

Abstract: Letter to the EditorThis document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…Also, not all possibilities for immediate blood coagulation activation were assessed, such as platelet aggregation, which was not altered in previous literature. 20 In conclusion, the current study found no evidence of immediate activation of the blood coagulation system 1-2 days following ChAdOx1 vaccination. ChAdOx1 leads to an inflammatory response with increased levels of IL-6, as seen previously with other types of vaccinations.…”
Section: Ta B L E 1 Baseline Characteristics and Medical Historycontrasting
confidence: 58%
“…Also, not all possibilities for immediate blood coagulation activation were assessed, such as platelet aggregation, which was not altered in previous literature. 20 In conclusion, the current study found no evidence of immediate activation of the blood coagulation system 1-2 days following ChAdOx1 vaccination. ChAdOx1 leads to an inflammatory response with increased levels of IL-6, as seen previously with other types of vaccinations.…”
Section: Ta B L E 1 Baseline Characteristics and Medical Historycontrasting
confidence: 58%
“…Following that, several cases of thrombotic events accompanied by thrombocytopenia have been observed and linked to the administration of the Oxford–AstraZeneca vaccine; Denmark, pursued by several European countries, was the first country to suspend the use of the Oxford–AstraZeneca vaccine [ 20 ]. Nevertheless, research data could not recognize platelet dysfunction in Oxford–AstraZeneca vaccinated population [ 21 , 22 ]. Therefore, the WHO and the European Medicines Agency declared that the trend of hypercoagulability could not be vindicated and recommended continued vaccination by the Oxford–AstraZeneca vaccine [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have explored the effect of ChAdOx1 administration on anti‐PF4 antibody positivity, reporting that in 1.2%–8% of vaccinated subjects anti‐PF4 antibodies were found, but always at a low titre and in no case inducing platelet activation 11,13–15 . Two other studies reported that ChAdOx1 vaccine administration did not induce hypercoagulability and did not alter platelet aggregation compared to unvaccinated controls 16,17 . One recent study, instead, reported that both ChAdOx1 and BNT162b2 enhance inflammation and platelet activation in healthy subjects, although in a more marked way for ChAdOx1 18 …”
Section: Introductionmentioning
confidence: 99%
“…11,[13][14][15] Two other studies reported that ChAdOx1 vaccine administration did not induce hypercoagulability and did not alter platelet aggregation compared to unvaccinated controls. 16,17 One recent study, instead, reported that both ChAdOx1 and BNT162b2 enhance inflammation and platelet activation in healthy subjects, although in a more marked way for ChAdOx1. 18 However, to date no studies have assessed whether an immunological response involving platelets develops in healthy subjects after adenoviral-vector or mRNA-based vaccine administration and if this associates with platelet activation.…”
Section: Introductionmentioning
confidence: 99%